Nature's Champion : B. W. Wells, Tar Heel Ecologist - Troyer, James R. (Book collections on Project MUSE., 1993)
Through the pioneering efforts of ecologist B.W. Wells (1884-1978), thousands of North Carolinians learned to appreciate and protect the state's diverse plant life long before ecology and conservation became popular causes. A keen observer of the natural landscape, Wells provided the first scientific descriptions in modern terms of the forces that shaped coastal communities, bogs and savannahs, the Carolina bays, pine forests, old fields, and mountain grassy balds. But the broader impact of his life lay in his championship and popularization of nature. Outside academic circles.